Relationships between mother's attitude, parenting style, communication competence, and maternal treatment style with deaf children's self-esteem in Iran high schools for the deaf - Sardar, Effat Hamed (2012)
This study examines the relationship between mothers’ attitude,communication competence, parenting styles and self-esteem among deaf children who are currently enrolled in Iranian high schools for the deaf. Previous studies among deaf children have explored into factors such as types of education, parents’ role, deaf parents’ impact, the severity of deafness, age of onset, deaf child’s communication at home and kinds of hearing aid used (Crocker & Luhtanen, 2008). Other variables such as family’s attitude, communication competence,and parental treatment styles have not been systematically explored. It is also not clear which factor affect deaf children’s self-esteem.This survey was conducted at four deaf high schools in Mashhad, Iran. The sample consisted of 200 deaf children (100 boys and 100 girls) and 200 hearing mothers.Four inventories were used in the study: (1) Rosenberg Self-Esteem Scale (to measure children’s self-esteem), (2) Parental Attitudes towards Deafness Scale (to measure mother’s attitude), (3) Parental Acceptance, Neglect and Rejection Questionnaire (to measure parenting styles), and (4) Communication Competence Scale(to measure communication competence).The children answered three questionnaires:Rosenberg Self-Esteem Scale, Parental Acceptance, Neglect and Rejection Questionnaire and Communication Competence Scale; while the mothers responded to Parental Attitudes towards Deafness Scale and Communication Competence Scale. In addition, the researcher conducted in-depth interviews with four deaf children and their mothers. The results showed relationships between the mothers’ attitude and deaf children self-esteem (r=0.28, p<0.05). Moreover, A one way analysis of variance (ANOVA) indicated that that statistical significant differences were found among the deaf children’s self-esteem scores within the three groups (parental acceptance, neglect, rejection), [F (2,191) =61,257 p < 0.001]. There was comparison between the three types (Post hoc t-test) was significant. Also, there were a positive relationship between selfesteem and communication competence of deaf children (r=0.26, p<0.05). In addition, were found relationship between mothers’ communication competence and deaf children’s self-esteem (r=0.32, p<0.05). It was found that for both boys and girls, the level of selfesteem was higher for deaf children who were from high income of family [F (196, 4) =.3.01, p<0.05].No significant difference was found between genders in deaf children self-esteem [t (198) =.39. p>0.05). Finally mothers’ attitude, deaf children’s communication competence,and mothers’ communication competence were found to be predictive of self-esteem among deaf children. Understanding the source of deaf children’s self-esteem is important for it is the first step in developing self-esteem in deaf children. Helping professionals such as counselors and teachers should involve family members through counseling and coaching on how to manage their deaf children. The counselors can help hearing parents navigate through their feelings and reactions by acknowledging their feelings of disbelief, grief, guilt, and anger when there is a deaf child in the family.